PENGARUH PENDIDIKAN AGAMA ISLAM TERHADAP MORAL MORAL REMAJA - Jumaidi; Dahlawi Fath; Siti Patimah; M. Makhrus Ali; Latief Arung Arafah (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2023)
Islamic religious education has an important role in shaping the morals of adolescents. During adolescence, individuals are in a critical phase of development where moral and ethical values begin to form, especially within themselves. Islamic religious education teaches guidelines about good behavior, moral values, and ethical principles that direct teenagers to differentiate between right and wrong. Through learning these values, teenagers are expected to be able to develop positive characters such as honesty, responsibility and politeness, as well as avoid negative behavior. This study aims to analyze the influence of Islamic religious education on teenage morals using a survey method of a number of respondents. The results of the research show that Islamic religious education significant. In improving adolescent morality, especially in the aspects of discipline, empathy and social behavior. Therefore, Islamic religious education is an important factor in moral development, teenagers who are moral and able to behave in accordance with religious teachings and social values